The Impact of Heavy Metal Accumulation on Agricultural Soils and Its Mitigation - Rabha, Sonia; K.V., Dhaneesh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Heavy metal contamination in various fields such as agricultural soils create severe global challenges affecting crop health, productivity, and overall ecosystem stability. This review investigates the source effects of heavy metals, which initially accumulate due to industrial activities and chemicals used during farming. The excessive presence of these metals can disrupt normal plant metabolism and reduce their growth. Furthermore, these metals can penetrate the food chain, posing serious health risks to humans and animals. Recent advancements in mitigating heavy metal pollution have been found, such as phytoremediation and biotechnological innovations offering promising solutions. Also, sustainable approaches utilizing microbial enzymes, microalgae, and bio-char-based technologies have shown high efficiency in removing heavy metals from contaminated environments. Further biosensors for detecting metal contamination provide sensitive, portable, and cost-effective alternatives. Overall, this review emphasizes the urgent need for awareness and continued research.